A Study of the ISO Certification Process in the Department of repair shop of the Companhia do Metropolitano in São Paulo - Neto, Diamantino Augusto Sardinha; Silva, Dirceu da (Review of Business Management, 2007)
This study aims to investigate how was the ISO 9002 certification process in the Repair Department of the Companhia do Metropolitano de São Paulo – Metrô, in the Wheeling Material process, focusing the evaluation of the process lived by the direct participants. The survey has been performed among the Department employees’ in order to study the group’s impression on the certification and its results. The data analysis allowed verifying the employees’ perception on the process and identifying the changes with the certification mainly with reference to documentation, organization and maintenance procedures. With this work we intend to contribute for further studies on certification in accordance with ISO 9000 requirements and its effects on the organizations, specially the ones with mixed economy, like this that was the subject of this research. Key-words: Standards ISO 9000. Certification process. Changes in the organization.